The Antibacterial Effects of New N-Alkylpyridinium Salts on Planktonic and Biofilm Bacteria - Hympanova, Michaela; Terlep, Saša; Markova, Aneta; Prchal, Lukáš; Dogsa, Iztok; Pulkrabkova, Lenka; Benkova, Marketa; Marek, Jan; Stopar, David (Frontiers in Microbiology, 2020)
An increasing microbial resistance to known antibiotics raises a demand for new antimicrobials. In this study the antimicrobial properties of a series of new N-alkylpyridinium quaternary ammonium compounds (QACs) with varying alkyl chain lengths were evaluated for several nosocomial pathogens. The chemical identities of the new QACs were determined by NMR, LC-MS and HRMS. All the planktonic bacteria tested were susceptible to the new QACs as evaluated by MIC and MBC assays. The antimicrobial effect was most pronounced against Staphylococcus aureus clinical isolates. Live/dead staining CLSM was used to test the effectiveness of the QACs in biofilms. The effectiveness was up to 10 fold lower than in the plankton. When QACs were used as irrignats in photoacoustic streaming, their effectiveness significantly increased. The combined use of irrigants and photoacustic streaming increased biofilm removal from the surface and increased the killing rate of the cells remaining on the surface. This may allow for a shorter chemical exposure time and lower dosage of quaternary ammonium compounds used in applications. The results demonstrate that the new QACs have potential to be applied as antibacterial compounds effective against planktonic and biofilm bacteria as well as irrigants in removal of difficult-to-reach biofilms.